2020
DOI: 10.1111/dme.14226
|View full text |Cite
|
Sign up to set email alerts
|

State of the art: understanding and integration of the social context in diabetes care

Abstract: We review the past 25 years of research addressing challenges people living with diabetes experience in their daily lives related to social contexts, i.e. in their family, at work and in society at large, and identify research gaps. We found that young people with diabetes, as they develop through to adulthood, are exposed to considerable risks to their physical and mental health. Family‐system interventions have had mixed outcomes. Research in this area would benefit from attention to ethnic/cultural diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 47 publications
(70 reference statements)
0
31
0
2
Order By: Relevance
“…According to Sullivan-Bolyai et al (2014), the parent-adolescent relationship should be characterised by interdependence, with parents "striking a balance but still in the driver's seat," as shared responsibility has been found to be associated with better glycemic control (Marker et al, 2018;Young et al, 2014). Studies have shown that the opposite can have negative consequences; parental over-involvement affects diabetes outcomes negatively, while under-involved parents can also be the cause of poor diabetes control (Keough et al, 2011;Marker et al, 2018;de Wit et al, 2020;Young et al, 2014). Thus, striking a balance in parental involvement in diabetes management is crucial.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Sullivan-Bolyai et al (2014), the parent-adolescent relationship should be characterised by interdependence, with parents "striking a balance but still in the driver's seat," as shared responsibility has been found to be associated with better glycemic control (Marker et al, 2018;Young et al, 2014). Studies have shown that the opposite can have negative consequences; parental over-involvement affects diabetes outcomes negatively, while under-involved parents can also be the cause of poor diabetes control (Keough et al, 2011;Marker et al, 2018;de Wit et al, 2020;Young et al, 2014). Thus, striking a balance in parental involvement in diabetes management is crucial.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Because management of type 1 diabetes is carried out in the context of daily life, diabetes affects and disrupts family life (Kingod & Grabowski, 2020;Marshall et al, 2009;de Wit et al, 2020). Christie (2019) found that young people with type 1 diabetes view diabetes as a family illness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations